MIMO CPW-Fed Bent Antenna Based USB Dongle for ECMA-368 WPANs - Beddiafi, Y.; Abed, D.; Boualleg, A.; Mehallel, E. (Advanced Electromagnetics, 2021)
A multiple-input-multiple-output (MIMO) ultra-wideband (UWB ) printed bent antenna, suitable for MB-OFDM ECMA-368 system integration with the wireless universal serial-bus (WUSB) dongle is proposed. The antenna consists of two antenna elements with an overall area of 18 X 53 mm2. Each antenna element is a simple modified folded-monopole fed by a coplanar waveguide (CPW). The design process of proposed MIMO UWB CPW-fed bent antenna configuration is presented in four simple steps. Experimental results show that the proposed design has a good impedance bandwidth in the range of 2.95–18.55 GHz with 147.2% fractional bandwidth (FBW). Moreover, the proposed antenna enjoys, low envelope correlation coefficient (ECC), good diversity gain (DG), low total active reflection coefficient (TARC) and omnidirectional radiation patterns. The bit error rate (BER) of the overall MB-OFDM ECMA-368 system with the existence of the proposed MIMO UWB CPW-fed bent antenna is evaluated in more realistic transmission channel scenario by using the extracted transmitting and receiving UWB antennas transfer functions.